Case report: Diagnosis of impaired consciousness in a cancer patient using immune checkpoint inhibitors - Cathalifaud, Daniel; Basáez, Cristóbal; Yáñez, Tatiana (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) are drugs that are being increasingly used in the field of oncology; due to their mechanism of action, they can present immune-related adverse effects (IRAEs), with various clinical manifestations, one of which is delirium. We present the case of a patient diagnosed with pleural mesothelioma that started combined palliative immunotherapy two months before admission. She was hospitalized for delirium with psychotic symptoms and a comprehensive neurological and etiological examination for this pathology was performed, revealing undetectable TSH levels, indicating the etiology of the condition as thyrotoxicosis in the context of autoimmune thyroiditis, secondary to treatment with ICIs. Symptomatic treatment with beta-blockers was initiated, leading to progressive improvement. This case brings awareness of impaired consciousness and neuropsychiatric symptoms as manifestation of IRAEs and the difficulty of their diagnosis: there may also be several other causes of impaired consciousness, so the characterization of delirium requires a multifaceted approach to determine the underlying cause, taking into account direct cancer-related complications and those stemming from the treatments received by this group of patients. Endocrinological immune-related adverse events (IRAEs), such as thyroid IRAEs, generally have a low lethality rate, do not necessarily require discontinuation of therapy, and are linked to a more favorable oncological prognosis. Conversely, neurological IRAEs, though rare, constitute a contraindication for further use of ICIs. This clinical case emphasizes the importance of the systematic study of consciousness impairment in cancer patients, and of considering multiple IRAEs that could lead to changes in oncological therapy when establishing possible etiologies.